Collaboration technologies and social computing : 9th International Conference, CollabTech 2017, Saskatoon, SK, Canada, August 8-10, 2017, proceedings /: 9th International Conference, CollabTech 2017, Saskatoon, SK, Canada, August 8-10, 2017, proceedings. (2017) - Unknown
No abstract available